Building defect detection: External versus internal thermography. (15th August 2016) - Fox, Matthew; Goodhew, Steve; De Wilde, Pieter
Abstract: Many buildings suffer from defects in the building envelope, such as missing insulation, thermal bridging, cracks and moisture problems. Thermography is one technology that can help to identify such defects. However, there are different approaches towards assessing the building envelope. Pass-by thermography is an emerging method, which is used to capture single thermal images of external building elevations. Compared with traditional walk-through thermography, it is much quicker and cheaper to perform. Yet it is currently unclear how successful this methodology is at detecting building defects. This paper qualitatively compares pass-by thermography and walk-through thermography. A set of 122 residential dwellings in South West England was inspected using the both methodologies. Results show that substantially more defects were detected using walk-through thermography, with internal inspections yielding the greatest number of detected defects. Significant constraints with walk-past thermography were identified, such as unknown occupancy behaviour, transient climatic conditions, fixed viewing angles and spatial resolution limitations, which were all found to have a greater impact on image results than during walk-through thermography. Although trends in conductivity defects were found from target comparison analysis between similar dwellings, viewing single external elevations under walk-past thermography was found to miss many different defect types, which would have normally been discovered during traditional walk-through thermography. Highlights: We compare a pass-by thermography methodology with traditional walk-through thermography for building defect detection. Results illustrate how fewer building defects are detected using walk-past thermography compared with walk-through. Key constraints to walk-past thermography were identified and found to have a detrimental impact on image interpretation. Trends in defects were identified using walk-past thermography on dwellings with similar construction. A greater number and variety of defects were detected from inside dwellings than were detected from external inspections.